Strategic influence of Robinson and self questioner at progressing the reading comprehension for primary sixth class students (Journal Of Educational and Psychological Researches, 2015)
Recent research looking for acknowledgment of strategically influence of Robinson and self question at progressing the reading comprehension for students of sixth class .To achieve research goal so the researcher mentally chose primary sixth class  at  the school (Tashti the primary) that followed education directorate of province (Jamjamal)/Suliymania for the scholastic year 2012-2013 as application field for their experiment of boys' number reached to (95) (female and male)students in reality (32) of the first experimental group and (31) student (female and male) from controlled group, the researcher rewarded between of three variable groups (timing period, intelligence ,Kurdish language degrees for the previous scholastic year).The experiment continued as full semester (first term) wherein the teacher has been  taught the item of three researches groupsAnd prepared of typical and statistical test of reading comprehension consists of (35) clause from the test type as multi and repeating of words arrangements and for their mixing and complementary and upon specified with honest and firm and the researcher used the statistical methods as follow: the analyzing of unique contraction and the equivalent of difficulty coefficient  and the equivalent of Codur Richardson and the equivalent of  the wrong alternatives activity and the experiment finished of the resultant implementation test and the research's results were discharged and showed the first experimental group that studied the reading item according to Robinson strategies and the second experimental strategies that studied the reading item according to self questioning strategy on the controlled group as showed for no differentiation between the first and second group